2020
DOI: 10.3390/diagnostics10040203
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Japanese Version of the Ocular Surface Disease Index and Dry Eye-Related Quality-of-Life Score for Dry Eye Symptom Assessment

Abstract: The aim of this study was to compare patient-reported symptoms of dry eye disease (DED) between the Japanese version of the Ocular Surface Disease Index (J-OSDI) and the Dry Eye-Related Quality-of-Life Score (DEQS). A total of 169 participants were enrolled between September 2017 and May 2018. Patients were administered the J-OSDI and DEQS questionnaires at their first (baseline) and follow-up visits to evaluate DED-related symptoms. The correlations between the J-OSDI total score and DEQS (Frequency and Degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…This study demonstrated that the DEQS-Th questionnaire has a criterion (concurrent) validity with the OSDI, consistent with a related study by Inomata et al that demonstrated a strong correlation between the DEQS and the Japanese version of OSDI (J-OSDI) scores. They found that the J-OSDI scores tended to be higher than the DEQS (31.6 vs. 27.6) which was in accordance with our study [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…This study demonstrated that the DEQS-Th questionnaire has a criterion (concurrent) validity with the OSDI, consistent with a related study by Inomata et al that demonstrated a strong correlation between the DEQS and the Japanese version of OSDI (J-OSDI) scores. They found that the J-OSDI scores tended to be higher than the DEQS (31.6 vs. 27.6) which was in accordance with our study [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, the DEQS may be cumbersome for respondants because it requires responding to up to 30 questions, compared with the 12 questions in the OSDI. Nevertheless, a recent study showed that the OSDI and the DEQS are significantly correlated, with negligible score differences [ 22 ]. This evidence affirms the use of the DEQS-Th as a valid method to assess subjective dry eye symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The internal consistency of the app-based JACQLQ was assessed using Cronbach alpha coefficient, with an alpha score of >.70 considered acceptable [ 20 ]. Concurrent validity was assessed by calculating the correlations (Pearson coefficient) and mean differences (Bland-Altman analysis) [ 15 , 21 ].…”
Section: Methodsmentioning
confidence: 99%